Moving upstream in health promoting policies for older people with early frailty in England? A policy analysis. Issue 3 (July 2018) - Drennan, Vari; Walters, Kate; Avgerinou, Christina; Gardner, Benjamin; Goodman, Claire; Frost, Rachael; Kharicha, Kalpa; Iliffe, Steve; Manthorpe, Jill
Objectives: Globally, populations are rapidly ageing and countries have developed health promotion and wellbeing strategies to address increasing demand for health care and old-age support. The older population is not homogeneous however, and includes a large group in transition between being active and healthy to being frail, i.e. with early frailty. This review explores the extent to which policy in England has addressed this group with a view to supporting independence and preventing further progression towards frailty. Methods: A narrative review was conducted of 157 health and social care policy documents current in 2014–2017 at three levels of the health and social care system in England. Findings: We report the policy problem analysis, the shifts over time in language from health promotion to illness prevention, the shift in target populations to mid-life and those most at risk of adverse outcomes through frailty, and changes to delivery mechanisms to incentivize attention to the frailest rather than those with early frailty. We found that older people in general were not identified as a specific population in many of these policies. While this may reflect a welcome lack of age discrimination, it could equally represent omission through ageism. Only at local level did we identify some limited attention to preventative actions with people with early frailty. Conclusion: The lack of policy attention to older people with early frailty is a missed opportunity to address some of the demands on health and social care services. Addressing the individual and societal consequences of adverse experiences of those with the greatest frailty should not distract from a more distinct public health perspective which argues for a refocusing upstream to health promotion and illness prevention for those with early frailty.